Risk factors and clinical outcomes of cytomegalovirus infection following haploidentical hematopoietic stem cell transplantation in patients with aplastic anemia: a single-center retrospective study - Feng, Jia; Zhang, Xinhe; Tan, Zhengwei; Zhao, Yuechao; Hu, Huijin; Chen, Junfa; Wu, Liqiang; Yu, Qinghong; Wu, Dijiong; Ye, Baodong; Liu, Wenbin (Frontiers in Medicine, 2025)
BackgroundCytomegalovirus (CMV) infection remains a critical cause of mortality after allogeneic hematopoietic stem cell transplantation, despite significant advancements in CMV prevention and treatment with the introduction and widespread use of letermovir. However, in China, due to limitations in the availability and cost of medications, some patients still face challenges in accessing letermovir. For this subset of the population, exploring the risk factors for CMV infection remains significant in predicting its occurrence.MethodsTherefore, a retrospective analysis was conducted on 88 haploidentical hematopoietic stem cell transplant recipients over 4 years.ResultsOur study results indicate that chronic graft-versus-host disease (cGVHD) is an independent risk factor for CMV infection following haploidentical hematopoietic stem cell transplantation (Haplo-HSCT). Survival analysis reveals lower survival rates in the refractory CMV infection (RCI) group compared to the non-RCI group, with patients having lower viral loads demonstrating higher rates of seroconversion and improved survival under the same treatment regimen.ConclusionStrengthening the monitoring of CMV-DNA in post-transplant patients, actively promoting hematopoietic recovery, preventing the occurrence of CMV infection, and controlling the development of CMV infection can lead to better survival outcomes for patients with aplastic anemia undergoing Haplo-HSCT.